Multicultural Education in the Application of Learning History - Syarief, Thalia Natasya; Darmawan, Wawan (Lembaran Ilmu Kependidikan, 2024)
This research was carried out with the aim of finding out the application of multicultural education in history learning at school which is used as a basis for prioritizing attitudes of tolerance in the social life of students in their environment. This research applies the library study method in writing in which the author first collects relevant sources in the form of books, journals, ebooks and other reading sources that are appropriate to the topic being discussed. After the sources have been collected, the next stage is data analysis. In this research, the data analysis stage was carried out in several stages to produce valid data. The results of this research show that there is a close relationship between multicultural education and History learning in schools is used as an effort to instill multicultural awareness and also to unite various differences to establish safe, peaceful and happy coexistence. As a country with a lot of diversity in every part of its territory, Indonesia is called a multicultural country. This is also felt in the world of education, the cultural background of students is one of the factors that can trigger conflict in a multicultural society.